Pengaruh Akuntabilitas dan Transparansi Laporan Keuangan Terhadap Kepercayaan Donatur Pada Organisasi Nirlaba Yayasan Panti Asuhan di Kota Palembang - Intan Purnamasari Saputra; Mutiara Maimunah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
. The study aims to analyze the influence of accountability and transparency the financial report on the donor’s belief in the non-profit organization of the orphanage foundation in the city of Palembang. The data used is the primary data. The population in this study is all managerial parties involved in the process of creating financial reports on the orphanage foundation and its service units registered to the city’s Palembang social services. The sample retrieval technique used was a nonsampling method with a saturated sampling technique and was obtained 47 respondents. Hypothetical testing done with multiple linear regression analysis. Research shows that accountability does not affect the trust of the donor and transparency the financial report has a positive effect on the trust of the donor